The Impacts of Oil Palm Agriculture on Colombia's Biodiversity: What We Know and Still Need to Know. (September 2015) - Vargas, Lain Efren Pardo; Laurance, William F.; Clements, Gopalasamy Reuben; Edwards, Will
The inexorable expansion of oil palm plantations has been a major driver of biodiversity loss in the tropics. This is particularly evident in Malaysia and Indonesia, where the majority of the world's oil palm is cultivated. In Latin America oil palm acreage has also been steadily increasing, especially in countries such as Colombia, the largest producer by far. However, information on the biological implications of rapid land conversion to oil palm in the region remains scarce. Here, we review the state of knowledge about the impacts of oil palm on biodiversity in Colombia. We also discuss the conservation strategies that have been implemented in the country, and propose research that we need to develop best management practices. The vast majority of research has focused on biotechnology, soils, biological pest control, carbon stock and reduction of greenhouse gases emission, but research on biodiversity is very scarce, or is not published yet. However, important investment and research on this topic are being developed. The most threatened ecosystems are the savannas in the Orinoquia region, where most of the expansion is predicted. The demands for green markets and certification are slowly encouraging oil palm corporations to mitigate their 'biological footprint'. However, applied research on the possible impacts of oil palm on biodiversity are urgently needed to support conservation efforts in the oil-palm-dominated landscapes of Colombia, along with commitments by the government and companies to adopt the resulting recommendations.